PERSONAL BRANDING DEVELOPMENT STRATEGY FOR UMKM VILLAGE WANASABA LOR, WEST JAVA, INDONESIA - Ade Johar Maturidi; Lilis Suharti; Muangsal Muangsal; Moh Setiawan (Jurnal Abdisci, 2025)
Community service activities in Wanasaba Lor Village, Talun District, Cirebon Regency, aim to develop the social and cognitive sensitivity of lecturers and students and support the acceleration of development. This village is located in the lowlands with a dense population. This community service activity involves dividing the areas of two hamlets, namely Hamlet 1 and Hamlet 2, with a total of 20 RTs and 5 RWs. This village is located approximately 3.2 km from the sub-district and 2.4 km from the Cirebon district government center. Administratively, Wanasaba Lor Village is included in the semi-urban village category. Community service organizers chose Wanasaba Lor Village as the practice site, and a site inspection and communication with the village head was carried out to ensure agreement and support in realizing the development and welfare of the local community.